Vulnerability assessment of Angolan university web applications - Mateus, E.; Serrão, C. (Proceedings of the 17th International Conference on Web Information Systems and Technologies, 2021)
Vulnerability assessment is one of the technical procedures that can help prevent serious security breaches, which, when exploited, can undermine brand credibility and or the continuity of a business. Universities hold and process important relevant and sensitive student and staff information appealing to attackers and might affect the organisations' credibility if such information is disclosed. This work presents a study conducted to assess the security status of the Angolan universities' web applications, identifying the most frequent security vulnerabilities and their criticality, based on OWASP Top 10 and CWE Top 25 references to identify and validate the findings discovered during the automatic vulnerability assessment process.